"Logan circle arctic beauty" (Philadelphia Evening Bulletin, 1925)
"Another striking view of the Fountain, also looking toward City Hall, the high tower of which looms against a wintry sky. Philadelphia probably has nor more striking ice-picture than its frozen Parkway." With clipping